Preparation method of low-dimensional non-lead perovskite polymer composite material
Through the protic solvent-mediated microemulsion method, the chromophore nucleation crystallization problem caused by non-polar solvents during the mixing process is solved, the uniformity of the perovskite micro-nano structure is improved, the external quantum efficiency of the luminescent solar concentrator is enhanced, and high-performance and environmentally friendly LSCs devices are realized.
Patent Information
- Application Number
- CN202411932900.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-05-16
- Estimated Expiration
- 2044-12-26
AI Technical Summary
Non-polar solvents spontaneously promote nucleation of chromophores during mixing, resulting in random distribution of size and uniformity of micro-nano crystals, limiting the high-performance application of low-dimensional non-lead perovskite-polymer composites in luminescent solar concentrators.
Uniform crystal particles are obtained by milling non-lead low-dimensional perovskite single crystal material, dissolved in protic solvent to form mother liquor A, and dissolved the polymer material in a non-polar solvent to form mother liquor B. After preheating and stirring, the mixture is uniformly mixed to form a microemulsion of composite material, bubbles in the liquid are removed by vacuum extraction, and finally cured in a glass template to prepare a high-performance luminescent solar condenser.
It improves the uniformity of perovskite micro-nano structure, enhances the external quantum efficiency of luminescent solar concentrators, solves the barriers to distribution regulation of non-lead low-dimensional perovskites in composite materials, and realizes environmentally friendly and high-performance LSCs devices.
Smart Images

Figure CN120005604A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a low-dimensional non-lead perovskite polymer composite material, and in particular to a method for preparing a low-dimensional non-lead perovskite polymer composite material applied to the field of low-dimensional semiconductors. Background Art
[0002] Perovskite semiconductors have significant advantages in photovoltaic cells, light-emitting diodes, photodetectors and other fields due to their simple manufacturing costs and good optoelectronic properties. Compared with traditional three-dimensional perovskites, low-dimensional perovskite semiconductors have reliable environmental stability. By designing the spatial configuration of spacer molecules and the binding sites of local branches, the database of low-dimensional structures (two-dimensional, one-dimensional and zero-dimensional) that can be formed is greatly expanded, which provides a reliable theoretical basis and design strategy for regulating its emission spectrum band, exciton radiation efficiency, and electron transport mechanism. However, the lead ions contained in the general perovskite structure are eco-toxic, which is not conducive to the wide application of the corresponding low-dimensional structure in actual devices, such as the polymer-doped quasi-two-dimensional lead halide perovskite film and its preparation method and application disclosed in the specification of Chinese patent CN117683537A, and the lead halide perovskite nanocrystal-polymer film and its preparation method disclosed in the specification of Chinese patent CN113136043A. Therefore, the comprehensive design of high-performance low-dimensional non-lead perovskites has always been the research focus in this field.
[0003] In recent years, luminescent solar concentrators (LSCs) have developed rapidly. They can be integrated into the building environment "invisibly" without adversely affecting the aesthetics of the building or the quality of life of residents, becoming a potential advantage technology in the field of BIPV. LSCs are mainly embedded in prefabricated polymer or glass optical waveguide materials by doping or coating with high luminescence yield guest particles (chromophores). When working, direct or scattered photons are continuously absorbed and re-emitted by chromophores in the waveguide medium, and then guided to the edge of the waveguide, and finally drive the photovoltaic cells attached to the edge of the LSCs to generate electricity.
[0004] At present, most of the chromophores used in LSCs are mainly concentrated in the inorganic quantum dot system. However, the traditional inorganic quantum dot synthesis process requires a series of constraints such as high temperature and inertness, resulting in high energy consumption and poor yield. Based on this, low-cost and high-performance perovskite quantum dot materials have become new materials for future LSCs and have demonstrated good device performance. Despite this, due to the problems of easy agglomeration, hydrolysis, phase change, etc., LSCs based on perovskite quantum dots are still significantly restricted. In contrast, low-dimensional non-lead perovskites have excellent stability and extremely high quantum yields. They can maximize the indirect radiation pathway of self-trapped excitons and minimize the coupling of photon absorption and re-emission, which is expected to realize excellent performance and environmentally friendly LSCs devices.
[0005] The realization of targeted LSCs is usually based on the architecture of chromophore-polymer composites. Therefore, most polymer media and chromophore materials need to be dissolved in a uniform non-polar solvent (e.g., toluene) in an appropriate proportion in advance, and then cured in a mold of a certain size by heating / UV treatment to form a composite material. However, as an orthogonal solvent for the low-dimensional non-lead perovskite mother solution, the non-polar solvent will spontaneously promote the nucleation and crystallization of the chromophore during the mixing process, producing micro-nano crystals with random distribution of size and uniformity. The mixed solution prepared based on this will greatly limit the low-dimensional non-lead perovskite-polymer composites used for high-performance LSCs.
[0006] So far, there has been no relevant report on the solution of the above key problems in the composite material system. In view of this, it is urgent to develop relevant technologies to solve the dielectric dispersion problem of such perovskites in order to realize high-performance LSCs devices. Summary of the invention
[0007] In view of the above-mentioned prior art, the technical problem to be solved by the present invention is that the non-polar solvent, as an orthogonal solvent of the low-dimensional non-lead perovskite mother liquor, will spontaneously promote the nucleation and crystallization of the chromophore during the mixing process, producing micro-nano crystals with randomly distributed size and uniformity.
[0008] To solve the above problems, the present invention provides a method for preparing a low-dimensional non-lead perovskite polymer composite material, comprising the following steps: S1. uniform crystal particles are obtained by grinding non-lead low-dimensional perovskite single crystal materials; S2, dissolving the obtained crystal particles in a protic solvent to obtain a mother solution A; S3, dissolving the polymer material in a non-polar solvent to obtain a mother solution B; S4, preheating both the mother liquor A and the mother liquor B, and stirring for 10 minutes, the preheating temperature is 50°C, adding the mother liquor A to the mother liquor B in an appropriate proportion, maintaining the temperature at 50°C during mixing, and obtaining a microemulsion of the composite material after mixing evenly, and then vacuuming the microemulsion at a temperature of 50°C to remove bubbles in the liquid; S5. Pour a certain amount of the microemulsion into a glass template with a monitoring function. During pouring, the glass template is clamped and limited by a metal clamp, and the distribution of the microemulsion in the glass template is monitored. When the microemulsion is evenly distributed, the glass template is placed in a hot oven by a metal clamp and heated at 60° C. for 1 hour to solidify the microemulsion. After solidification, the glass template is removed, and then laser polished and ground to obtain a luminescent solar concentrator with high external quantum efficiency.
[0009] In the preparation method of the above-mentioned low-dimensional non-lead perovskite polymer composite material, a new proton solvent-mediated low-dimensional non-lead perovskite microemulsion method is provided to improve the dispersion problem of this type of perovskite in the mother liquid medium, improve the uniformity of the perovskite micro-nano structure, and thereby enhance the external quantum efficiency of the luminescent solar concentrator using this type of composite material, effectively solving the barriers of the current relevant technology to the distribution regulation of non-lead low-dimensional perovskite in composite materials.
[0010] As a further improvement of the present application, the protic solvent includes one or more of methanol, ethanol, and isopropanol, preferably isopropanol. The polymer material is at least one of polymethyl methacrylate (PMMA), polystyrene (PS), polycarbonate (PC), polydimethylsiloxane (PDMS), polyvinylidene fluoride or polyvinylidene fluoride (PCVDF), and the degree of polymerization of each polymer molecule ranges from 1 to positive infinity, and the polymer material is preferably polymethyl methacrylate with an average molecular weight of 120,000.
[0011] The non-polar solvent is an aromatic solvent, including at least one of chlorobenzene, toluene, p-xylene and o-dichlorobenzene.
[0012] As a further improvement of the present application, the general structural formula of the non-lead low-dimensional perovskite in step S1 is ApBqXr, in which: A is at least one of alkali metal cations (including Li+, Na+, K+, Rb+, Cs+), alkaline earth metal ions (including Be2+, Mg2+, Ca2+, Sr2+, Ba2+) and ammonium ions (including primary ammonium, secondary ammonium, tertiary ammonium, quaternary ammonium); B is Ge 2+ Sn 2+ , Sb 3+ 、Bi 3+ , Cu + / 2+ 、Zn + / 2+ 、Eu2 + / 3+ 、Ag + 、Au + at least one of; X is a halogen ion, mainly I - Br - , Cl - At least one of them can be selected, and p, q, and r are any positive integers.
[0013] As a further improvement of the present application, the structural formula of the non-lead low-dimensional perovskite is Bmp2SnBr4, wherein Bmp is 1-butyl-1-methylpiperidinium ion, which is a type of ammonium ion. The Bmp2SnBr4 material has significant self-trapped exciton luminescence characteristics and excellent luminescence performance, and is suitable as a chromophore for high-performance luminescent solar concentrators.
[0014] As a further improvement of the present application, the mother solution A is a single component of non-lead low-dimensional perovskite or a mixed component of any proportion. The concentration range of the mother solution A is 0.01 mg·mL -1 To 100mg·mL -1 Between, and preferably 20mg·mL -1 The concentration range of mother solution B is 10 mg·mL -1 To 1000mg·mL -1 Between and preferably 20 mg·mL -1 In step S4, the mixing volume ratio of mother liquor B and mother liquor A is 1-1000:1, preferably 100:1.
[0015] As a further improvement of the present application, the glass template includes two white glass plates, and rubber strips are sandwiched between the four edges of the two white glass plates. An injection pipe and two exhaust pipes are fixedly connected to the upper end of the top rubber strip, and the exhaust pipe and the injection pipe are both connected to the space surrounded by the two white glass plates. The injection pipe is located in the middle of the rubber strip, and the two exhaust pipes are respectively located at both ends of the rubber strip close to the edges of the white glass plates. Solenoid valves are installed on the two exhaust pipes, and an overflow detection unit is installed at the outer end of the exhaust pipe.
[0016] As a further improvement of the present application, the overflow detection unit includes an outer shell fixedly connected to the outer end of the exhaust pipe, the exhaust pipe is a hard transparent structure, a laser emitter is installed on the inner wall of the outer shell, and the laser emitting end of the laser emitter faces the exhaust pipe.
[0017] As a further improvement of the present application, the metal clamp includes a base plate, the upper end of the base plate is connected to two connecting rods through an electric slide rail, the tops of the two connecting rods are fixedly connected to sensing plates, the ends of the two sensing plates close to each other are fixedly connected to clamps, the sensing plate includes a back plate, a covering plate and a miniature interlayer fixedly connected therebetween, the covering plate is connected to the clamp, and a pressure sensor is fixedly installed on the back plate toward the middle of the clamp.
[0018] As a further improvement of the present application, the miniature interlayer is made of elastic material, and a plurality of guide rods are fixedly connected to one end of the cover plate close to the back plate. A plurality of corresponding guide holes are drilled on the miniature interlayer and the back plate, and the guide rods movably penetrate the corresponding guide rods. Detection holes are drilled in the middle of the miniature interlayer, the cover plate and the splint, and the detection holes are coaxially arranged with the pressure sensor.
[0019] As a further improvement of the present application, the detection end of the pressure sensor is located in the detection hole on the clamping plate, and the distance between the detection end and the edge of the mouth of the detection hole away from the sensing plate is 1-2 mm.
[0020] In summary, a new proton solvent-mediated microemulsion method for low-dimensional non-lead perovskite is provided to improve the dispersion problem of this type of perovskite in the mother liquid medium, improve the uniformity of the perovskite micro-nanostructure, and thereby enhance the external quantum efficiency of the luminescent solar concentrator using this type of composite material, effectively solving the barriers of the existing technology to the distribution regulation of non-lead low-dimensional perovskite in composite materials, and the luminescent solar concentrator based on non-lead low-dimensional perovskite abandons the introduction of traditional lead metal, has high environmental protection and low environmental harm, and at the same time has low cost and stable device output power, which is suitable for commercial building integrated photovoltaic products, including but not limited to photovoltaic windows / roofs / curtain walls, etc., and is conducive to the development of zero-carbon building field. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the main flow chart of this application; Figure 2 The fluorescence spectrum and corresponding external quantum efficiency obtained by testing the microemulsion according to the first embodiment of the present application; Figure 3 The fluorescence spectrum and corresponding external quantum efficiency obtained by testing the luminescent solar concentrator obtained in the first embodiment of the present application, as well as the attenuation diagram compared with the microemulsion; Figure 4 A JV curve and efficiency diagram under standard sunlight obtained by testing when the edge of the obtained luminescent solar concentrator is constructed into an LSC photovoltaic power generation device in the first embodiment of the present application; Figure 5 The fluorescence spectrum and corresponding external quantum efficiency obtained by testing the microemulsion of the second embodiment of the present application; Figure 6 The fluorescence spectrum and corresponding external quantum efficiency obtained by testing the luminescent solar concentrator obtained in the second embodiment of the present application, as well as the attenuation diagram compared with the microemulsion; Figure 7 A JV curve and efficiency diagram under standard sunlight obtained by testing when the edge of the obtained luminescent solar concentrator is constructed into an LSC photovoltaic power generation device in the second embodiment of the present application; Figure 8 The JV curve and efficiency diagram of the LSC photovoltaic power generation device according to the third embodiment of the present application; Fig. 9 Schematic diagram of pouring microemulsion into a glass template in the first, second and third embodiments of the present application; Fig.10It is a partial schematic diagram of the overflow detection unit in the first, second and third embodiments of the present application; Fig.11 It is a right side stereoscopic diagram of the metal clamp in the first, second and third embodiments of the present application; Fig.12 It is a left side stereoscopic diagram of the metal clamp in the first, second and third embodiments of the present application; Fig.13 Exploded diagrams of the metal clamp parts in the first, second and third embodiments of the present application; Description of the numbers in the figure: 1 white glass plate, 2 rubber strip, 201 injection tube, 202 exhaust pipe, 3 outer shell, 301 laser emitter, 41 bottom plate, 42 connecting rod, 43 sensing plate, 431 back plate, 432 miniature interlayer, 433 cover plate, 44 splint, 401 guide rod, 402 guide hole, 5 pressure sensor. DETAILED DESCRIPTION
[0022] Three implementation modes of the present application are described in detail below with reference to the accompanying drawings.
[0023] The first implementation method: S1. The selected non-lead low-dimensional perovskite is a single crystal material of Bmp2SnBr4, and then the single crystal is ground with a mortar or a ball mill to obtain a crystal material with a size distribution in the range of 10nm-1000nm; S2. Take 20 mg of perovskite crystal material and place it in a glass flask, then add 1 mL of anhydrous ethanol, heat and stir at 50° C. for at least 20 minutes to fully dissolve the perovskite to form mother solution A, and keep it warm for use; S3, take 2000 mg of polymethyl methacrylate material and put it in a glass flask, then add 10 mL of chlorobenzene, heat and stir at 50°C for at least 1 hour to fully dissolve to form mother solution B, and keep warm for use; S4. The operation steps of the composite material microemulsion are as follows: take 1.0 mL of the B mother solution with a pipette and add it to a clean glass flask, then take 0.1 mL of the A mother solution with a pipette and add it to the flask, heat and stir at 50°C for at least 1 hour to mix evenly, and after sufficient dissolution, use vacuum pumping to remove bubbles in the solution to form a microemulsion, and keep it warm for use. The fluorescence spectrum and corresponding external quantum efficiency of the microemulsion obtained by testing are as follows: Figure 2 shown.
[0024] S5. Two white glass plates 1 (80mm*80mm*5mm) and four rubber strips 2 (80mm*10mm*6mm) are used to form a glass template. The rubber strips can be used as gaskets and seal the two white glass plates. The glass template is clamped and fixed by a metal clamp. A certain amount of microemulsion is added between the templates to fill them completely. Then, the template is placed in a hot oven and heated at 60°C for at least 1 hour to ensure that the internal material is completely cured. After taking it out, it is allowed to stand at room temperature to cool. Then, the two white glass plates 1 and the four rubber strips 2 are removed. The obtained luminescent solar concentrator is polished and grinded by laser processing. The size of the obtained luminescent solar concentrator is 50mm*50mm*6mm. The fluorescence spectrum and corresponding external quantum efficiency of the luminescent solar concentrator as well as the attenuation ratio compared with the microemulsion are tested, for example Figure 3 shown.
[0025] Afterwards, the perovskite solar cell panel was fixed to the edge of the luminescent solar concentrator prepared by the above process through a photocurable adhesive to construct an LSC photovoltaic power generation device. The JV curve and efficiency under standard sunlight were obtained. Figure 4 shown.
[0026] It is worth noting that when the present luminescent solar concentrator is used, commercial solar cells (silicon cells, cadmium telluride cells, perovskite cells, etc.) can be directly attached to the edge of the concentrator to ensure effective photovoltaic power output.
[0027] In step S5, Fig. 9 The glass template includes two white glass plates 1, and rubber strips 2 are sandwiched between the four edges of the two white glass plates 1. The upper end of the uppermost rubber strip 2 is fixedly connected with a filling pipe 201 and two exhaust pipes 202, and the exhaust pipes 202 and the filling pipe 201 are both connected to the space surrounded by the two white glass plates 1. The filling pipe 201 is located in the middle of the rubber strip 2, and the two exhaust pipes 202 are respectively located at both ends of the rubber strip 2 close to the edge of the white glass plate 1. Solenoid valves are installed on the two exhaust pipes 202, and an overflow detection unit is installed at the outer end of the exhaust pipe 202. Fig.10 The overflow detection unit includes an outer shell 3 fixedly connected to the outer end of the exhaust pipe 202. The exhaust pipe 202 is a hard transparent structure. A laser emitter 301 is installed on the inner wall of the outer shell 3. The laser emitting end of the laser emitter 301 faces the exhaust pipe 202. When pouring the microemulsion into the glass template, it can be poured into it through the injection pipe 201. During pouring, the two exhaust pipes 202 are used for exhaust. When the liquid level of the microemulsion reaches the top, part of the microemulsion will enter the exhaust pipe 202. At this time, the laser beam emitted by the laser emitter 301 will be blocked or weakened to a certain extent, thereby realizing the monitoring of the pouring of the microemulsion.
[0028] like Figure 11-12The metal fixture includes a bottom plate 41, the upper end of the bottom plate 41 is connected to two connecting rods 42 through an electric slide rail, the tops of the two connecting rods 42 are fixedly connected to a sensing plate 43, the ends of the two sensing plates 43 close to each other are fixedly connected to a clamping plate 44, the sensing plate 43 includes a back plate 431, a cover plate 433 and a miniature interlayer 432 fixedly connected therebetween, the cover plate 433 is connected to the clamping plate 44, the back plate 431 is fixedly installed with a pressure sensor 5 toward the middle of the clamping plate 44, when the laser transmitter 301 detects that the microemulsion enters the exhaust pipe 202, the solenoid valve can be controlled to close, so that the mouth of the exhaust pipe 202 is closed, and at this time, a small amount of microemulsion is continued to be injected to facilitate the promotion of the microemulsion It is redistributed between the two white glass plates 1, thereby effectively filling the unevenly filled or partially unfilled space, and then the microemulsion between the two white glass plates 1 is evenly distributed. As the microemulsion continues to fill, when the filling is saturated, an outward pushing force will be generated on the two white glass plates 1, thereby causing the miniature interlayer 432 to be slightly compressed to a certain extent, thereby causing the pressure sensor 5 to contact the white glass plate 1 and generate force data. When it generates data, the pouring of the microemulsion can be stopped and the next step can be continued. Through the above operation, the occurrence of uneven filling or non-filling when pouring the microemulsion can be effectively avoided, thereby effectively ensuring the quality of the obtained solar concentrator.
[0029] like Fig.13 The miniature interlayer 432 is made of elastic material, and a plurality of guide rods 401 are fixedly connected to one end of the cover plate 433 close to the back plate 431. A plurality of guide holes 402 corresponding to each other are drilled on the miniature interlayer 432 and the back plate 431, and the guide rods 401 movably penetrate the corresponding guide rods 401. Detection holes are drilled in the middle of the miniature interlayer 432, the cover plate 433 and the clamping plate 44, and the detection hole is coaxially arranged with the pressure sensor 5. The guide rods 401 and the guide holes 402 are mainly used for guiding and limiting, so that when the miniature interlayer 432 is slightly deformed due to force, the clamping plate 44 is not prone to radial deviation when it moves accordingly, thereby effectively ensuring its clamping stability on the glass template.
[0030] The detection end of the pressure sensor 5 is located in the detection hole on the clamping plate 44, and the distance between the detection end and the detection hole is 1-2mm away from the edge of the mouth of the sensing plate 43, so that when the microemulsion is not fully filled between the two white glass plates 1, the pressure sensor 5 is not easy to generate force data. After it is fully filled, the pressure sensor 5 can be easily triggered, thereby effectively ensuring the accuracy of monitoring the microemulsion filling situation during the pouring process.
[0031] The second implementation method: Different from the first embodiment, ethanol is used as the protic solvent in this embodiment, and other preparation conditions are consistent with the first embodiment. The corresponding data in the preparation process include the external quantum yield and decay ratio of the microemulsion and the luminescent solar concentrator, the JV curve and efficiency of the LSC photovoltaic power generation device. Figure 5-7 shown.
[0032] The third implementation method: Different from the first embodiment, the size of the prepared luminescent solar concentrator is 500mm*500mm*6mm, and the other preparation conditions are the same as the first embodiment. Compared with the first embodiment, the solar panel used has 10 cells connected in parallel on each side. The corresponding data include the JV curve and efficiency of the LSC photovoltaic power generation device. Figure 8 shown.
[0033] In view of current practical needs, the above-mentioned implementation mode adopted in this application is not limited to the scope of protection. Various changes made within the knowledge scope of technical personnel in this field without departing from the concept of this application still fall within the scope of protection of the present invention.
Claims
1. A method for preparing a low-dimensional non-lead perovskite polymer composite material, characterized in that: The following steps are involved: S1. uniform crystal particles are obtained by grinding non-lead low-dimensional perovskite single crystal materials; S2, dissolving the obtained crystal particles in a protic solvent to obtain a mother solution A; S3, dissolving the polymer material in a non-polar solvent to obtain a mother solution B; S4, preheating both the mother liquor A and the mother liquor B, and stirring for 10 minutes, the preheating temperature is 50°C, adding the mother liquor A to the mother liquor B in an appropriate proportion, maintaining the temperature at 50°C during mixing, and obtaining a microemulsion of the composite material after mixing evenly, and then vacuuming the microemulsion at a temperature of 50°C to remove bubbles in the liquid; S5. Pour a certain amount of the microemulsion into a glass template with a monitoring function. During pouring, the glass template is clamped and limited by a metal clamp, and the distribution of the microemulsion in the glass template is monitored. When the microemulsion is evenly distributed, the glass template is placed in a hot oven by a metal clamp and heated at 60° C. for 1 hour to solidify the microemulsion. After solidification, the glass template is removed, and then laser polished and ground to obtain a luminescent solar concentrator with high external quantum efficiency.
2. The method for preparing a low-dimensional non-lead perovskite polymer composite material according to claim 1, characterized in that: The protic solvent includes one or more of methanol, ethanol, and isopropanol; The polymer material is at least one of polymethyl methacrylate, polystyrene, polycarbonate, polydimethylsiloxane, polyvinylidene fluoride or polyvinylidene fluoride, and the degree of polymerization of each polymer molecule ranges from 1 to positive infinity; The non-polar solvent is an aromatic solvent, including at least one of chlorobenzene, toluene, p-xylene and o-dichlorobenzene.
3. The method for preparing a low-dimensional non-lead perovskite polymer composite material according to claim 1, characterized in that: The general structural formula of the non-lead low-dimensional perovskite in step S1 is ApBqXr, in which: A is at least one of an alkali metal cation, an alkaline earth metal ion and an ammonium ion; B is Ge 2+ Sn 2+ , Sb 3+ 、Bi 3+ , Cu + / 2+ 、Zn + / 2+ 、Eu2 + / 3+ 、Ag + 、Au + at least one of; X is a halogen ion, and p, q, and r are any positive integers.
4. The method for preparing a low-dimensional non-lead perovskite polymer composite material according to claim 3, characterized in that: The structural formula of the non-lead low-dimensional perovskite is Bmp2SnBr4, wherein Bmp is 1-butyl-1-methylpiperidinium ion.
5. The method for preparing a low-dimensional non-lead perovskite polymer composite material according to claim 3, characterized in that: The mother solution A is a single component of non-lead low-dimensional perovskite or a mixed component in any proportion, and the concentration range of the mother solution A is 0.01 mg·mL -1 to 100 mg·mL -1 The concentration range of the mother solution B is 10 mg·mL -1 to 1000 mg·mL -1 In step S4, the mixing volume ratio of mother liquor B to mother liquor A is 1-1000:
1.
6. The method for preparing a low-dimensional non-lead perovskite polymer composite material according to claim 1, characterized in that: The glass template comprises two white glass plates (1), and rubber strips (2) are sandwiched between the four edges of the two white glass plates (1); an injection pipe (201) and two exhaust pipes (202) are fixedly connected to the upper end of the uppermost rubber strip (2), and the exhaust pipes (202) and the injection pipe (201) are both in communication with a space enclosed by the two white glass plates (1); the injection pipe (201) is located in the middle of the rubber strip (2), and the two exhaust pipes (202) are respectively located at two ends of the rubber strip (2) close to the edge of the white glass plate (1); solenoid valves are installed on the two exhaust pipes (202), and overflow detection units are installed at the outer ends of the exhaust pipes (202).
7. The method for preparing a low-dimensional non-lead perovskite polymer composite material according to claim 6, characterized in that: The overflow detection unit comprises an outer shell (3) fixedly connected to the outer end of an exhaust pipe (202); the exhaust pipe (202) is a hard transparent structure; a laser emitter (301) is installed on the inner wall of the outer shell (3); a laser emitting end of the laser emitter (301) faces the exhaust pipe (202).
8. The method for preparing a low-dimensional non-lead perovskite polymer composite material according to claim 7, characterized in that: The metal fixture comprises a bottom plate (41), the upper end of the bottom plate (41) is connected to two connecting rods (42) via an electric slide rail, the tops of the two connecting rods (42) are fixedly connected to sensing plates (43), the ends of the two sensing plates (43) close to each other are fixedly connected to clamping plates (44), the sensing plates (43) comprise a back plate (431), a cover plate (433) and a miniature interlayer (432) fixedly connected therebetween, the cover plate (433) is connected to the clamping plate (44), and a pressure sensor (5) is fixedly mounted on the back plate (431) towards the middle of the clamping plate (44).
9. The method for preparing a low-dimensional non-lead perovskite polymer composite material according to claim 8, characterized in that: The miniature interlayer (432) is made of elastic material, and one end of the cover plate (433) close to the back plate (431) is fixedly connected to a plurality of guide rods (401), and the miniature interlayer (432) and the back plate (431) are both provided with a plurality of guide holes (402) corresponding to each other, and the guide rods (401) movably penetrate the corresponding guide rods (401), and the middle parts of the miniature interlayer (432), the cover plate (433) and the clamping plate (44) are all provided with detection holes, and the detection holes are coaxially arranged with the pressure sensor (5).
10. The method for preparing a low-dimensional non-lead perovskite polymer composite material according to claim 9, characterized in that: The detection end of the pressure sensor (5) is located in the detection hole on the clamping plate (44), and the distance between the detection end and the edge of the mouth of the detection hole away from the sensing plate (43) is 1-2 mm.
Citation Information
Patent Citations
Lead halide perovskite nanocrystalline-polymer film and preparation method thereof
CN113136043A
Polymer-doped quasi-two-dimensional lead halide perovskite thin film as well as preparation method and application thereof
CN117683537A
Solar fluorescent condenser and preparation method thereof
CN109244183A
Solar light condensation plate based on quantum dot-phosphorescent organic molecule hybrid material
CN110896111A
Preparation and application of sandwich-type solar light collector based on photonic crystal
CN113759531A